Sustainable Cities Towards A Green, Resilient and Inclusive Recovery : Applying the Sustainable Cities Implementation Framework in Bulgaria, Croatia, Poland, and Romania - World Bank (Washington, DC, 2022)
Cities are key to unlocking a climate-smart future for all, as they account for more than 50 percent of the global population, about 70 percent of global energy-related CO2 emissions and 80 percent of global GDP. Urban centers’ share of emissions is expected to grow as the urban population is projected to increase by 2.3 billion people by 20502. As the world recovers from the COVID-19 crisis, cities will present a huge opportunity to rebuild in a way that is climate friendly and meets some of the world’s ambitious climate targets. Cities are viewed as the source of and the solution to many of today's economic, social, and environmental challenges. This is not only because of the concentration of population and economic assets in urban areas, but also because local authorities perform key functions that impact the quality of life of their residents. From an urban management perspective, the leading resource and knowledge sharing platform is the GEF funded Global Platform for Sustainable Cities (GPSC), hosted by the World Bank. The GPSC states that achieving sustainability requires the balanced accomplishment of outcomes against four pillars, namely (1) robust economic growth, prosperity, and competitiveness across all parts of the city; (2) protection and conservation of ecosystems and natural resources into perpetuity; (3) mitigation of greenhouse gas (GHG) emissions while fostering overall city resilience; and (4) inclusiveness and livability, mainly through the reduction of city poverty levels and inequality. The Urban Sustainability Framework (USF), developed to outline the areas of work and support by the GPSC, offers a very useful representation of both outcomes as well as enabling actions and requirements (such as spatial data and good governance) cities could focus on.